Did internet usage reduce the impact of COVID-19 on the mental health of middle-aged and older adults? A difference-in-differences study based on CFPS data - Yang, Bo; Wang, Xiaofeng; Zhao, Yuan (Frontiers in Psychology, 2024)
Mental health is the cornerstone of public health, especially where middle-aged and older adults during the COVID-19 pandemic were concerned. The impact of Internet usage on mental health in the time of the crisis still presents a mixed picture. This study employs the PSM-DID method according to longitudinal data (CFPS) to explore whether Internet usage reduced the impact of COVID-19 on the mental health of middle-aged and older adults. The results reveal that Internet use improves the mental health of middle-aged and older adults in China, but that the impact varies between urban and rural residents. Greater marginal gains may be realized by enhancing the digital capacity of and narrowing the digital divide that exists among rural residents. Furthermore, the moderator effects model shows that people's perceptions of the Internet have an impact upon the length of time spent online and its consequent effect on mental health. The enhancement of digital capacity and proper guidance in digital education should be taken into consideration where the mental health of middle-aged and older adults is at issue.